2020
DOI: 10.48550/arxiv.2008.04264
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low-rank tensor reconstruction of concentrated densities with application to Bayesian inversion

Abstract: Transport maps have become a popular mechanic to express complicated probability densities using sample propagation through an optimized pushforward. Beside their broad applicability and well-known success, transport maps suffer from several drawbacks such as numerical inaccuracies induced by the optimization process and the fact that sampling schemes have to be employed when quantities of interest, e.g. moments are to compute. This paper presents a novel method for the accurate functional approximation of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Usually, again sampling methods are used for this often high-dimensional problem, the most popular of which certainly is the Markov chain Monte Carlo method. Nevertheless, recently some developments took place which showed that functional approximations of (posterior) densities are feasible and may prove beneficial in terms of convergence rates [11,48], see also [25,49] for different low-rank techniques.…”
Section: Numerical Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Usually, again sampling methods are used for this often high-dimensional problem, the most popular of which certainly is the Markov chain Monte Carlo method. Nevertheless, recently some developments took place which showed that functional approximations of (posterior) densities are feasible and may prove beneficial in terms of convergence rates [11,48], see also [25,49] for different low-rank techniques.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…In UQ this task arises for example in the parameter reconstruction of model data via inverse problems [7][8][9]. If a functional representation of exppℓpy; δqq can be constructed, it may for instance be used to efficiently generate independent posterior samples [10] or to compute highdimensional quantities of interest such as moments or marginals [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some details on different tensor formats and numerical algorithms can be found in [30][31][32][33]. Our focus lies on the TT format [33], which has been used with tremendous success for the solution of parametric PDEs and related UQ problems such as Bayesian inversion and random field representations, see [34][35][36][37][38]. ASGFEM in hierachical tensor formats are presented in [2,39] for affine coefficients.…”
Section: Introductionmentioning
confidence: 99%